UPHOLDING STUDENTS"™ SPEAKING SKILLS THROUGH VOGUE VIDEOBLOGS (VLOGS) - Suwarjo, Salma Nafiza Rahma; Izzah, Lidiyatul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aimed to investigate the effectiveness of Vogue vlogs used as media in teaching and learning English speaking skills. There were 36 students of grade XI Science occupied in one class, participated in this study as sample. The research was conducted at SMA Negeri 16, Bekasi Barat, West Java, in even semester of academic year 2023/2024. This study was mixed-methods research with explanatory sequential research design. The tools used to collect the data were tests and interview. The data were firstly analyzed quantitatively followed by qualitative data analysis. Quantitative data were analyzed by using paired sample t-test, while qualitative data were analyzed by using thematic analysis. Quantitative data analysis showed that students"™ speaking proficiency improved up to 19.58 points after they studied by using Vogue vlogs. Besides, the significance value (2 tailed) of 0.000 was lower than ð›¼ = 0.005, in the significance level of 5%. Meanwhile, qualitative analysis revealed that the students were getting more motivated and encouraged to practice their speaking through Vogue vlogs. These findings confirmed that Vogue vlogs were said to be effective to uphold students"™ speaking skills. This research, hence, rejected H0 and accepted Ha.